Detecting Geothermal Resources in a Plateau Area: Constraints From Land Surface Temperature Characteristics Using Landsat 8 Data - Dong, Ben; Dong, Shuyi; Wang, Yingchun; Wen, Fayang; Yu, Chunmei; Zhou, Jinlin; Song, Rongcai (Frontiers in Earth Science, 2022)
Land surface temperature (LST) is an important geophysical parameter. Extraction of ocean temperature with satellite remote sensing data is relatively mature and can reach 1K accuracy globally. Since the mountain surface is much more complex than the ocean surface, the accuracy of the mountain surface temperature retrieval is low, and the mountain surface temperature retrieval has become an urgent scientific problem to be solved. In this paper, the characteristics of surface temperature retrieval methods are systematically reviewed, based on Landsat 8 remote sensing data, the differences among these three algorithms are researched by adopting them to detect the surface temperature in the study area, where is Kangding county, Sichuan Province, China, then the experimental results of the three algorithms are verified by using the long-time(more than one year) measured data of the two monitoring sites, and the monitoring sites situate in Zhonggu Village area and Lao Yulin area of Kangding county. The results show that Radiative Transfer Equation (RTE) has the highest accuracy and the mean error is 0.372°C. The second is Mono-Window Algorithm (MW), with a mean error of -0.606°C, while the Split window algorithm (SW) has the lowest accuracy, with a mean error of -2.07°C. The experimental results were used to select an algorithm with relatively high accuracy and low sensitivity, and a time series was used to perform temperature retrieval for this study area from November 2016 to December 2017 to fully and thoroughly evaluate the applicability of the method. The result shows RTE has the highest accuracy in mid-winter and a relatively low accuracy in summer in Kangding county. The purpose of this paper is to establish a suitable method for high-precision surface temperature retrieval in plateau areas, and to provide technical support for exploring geothermal resources or evaluating geothermal potential in these areas.